The Influence Of NPM, EPS, Tattoos On Stock Price Of Banking Companies Listed On The IDX For The 2020-2022 Period - RAHAYU, Irana Liani; ADDINI, Zahrian Faradiza; YUSRIYYAH, Fauziah Nuur Nabilah (PT Keberlanjutan Strategis Indonesia, 2023)
In today's business world, which is developing rapidly, many investors are interested in investing their funds in stocks because it promises higher returns, both from dividends and capital gains. Before investing, an investor must know and choose which stocks can provide optimal returns for the funds invested. The capital market is a place for buying and selling transactions of various long-term instruments, including stocks. This study aims to empirically test and prove the effect of NPM, EPS, and TATO on stock prices for the 2020-2022 period. The following research uses a quantitative approach and multiple linear regression analysis with data processing using the tools of the Stata 15 program. The sampling method uses a purposive sampling technique. The sample of this research consisted of 18 companies. The results of the study by conducting the t-test showed that the NPM and TATO variables did not have a significant effect on stock prices, with an NPM probability value of 0.224; TATO with a probability value of 0.807, while the EPS variable has a significant effect on stock prices, with a probability value of 0.034, meaning that this value when compared to the ???? value, which is 0.05, is less significant. The f test states that the NPM, EPS, and TATO variables simultaneously influence stock prices based on a probability value of 0.0058, which means it is smaller than ???? of 0.05.